The Use of Twitter in Multiplying TV-online Visitor (Study Case: Telkom UseeTV) - Mashari, Imam; Iskandar, Budi Permadi (The Indonesian Journal of Business Administration, 2013)
The tight of competition in telecommunication industry encourages PT. Telkom to develop their core business into information, media, and edutainment area. Therefore, PT. Telkom launched UseeTV service. UseeTV is an over-the-top service based on website where customers can watch TV and video, as well as listen to radio anytime and every time. UseeTV stray to young man and netizen as their target market. In another case, the increasing life style of young man and netizen in accessing social media, especially Twitter can be an opportunity for UseeTV to build brand awareness in society. There are many ways to do campaign in Twitter. In this research, it discusses how Twitter campaign can increase the number of UseeTV’s website visitor. The Twitter campaign was executing by creating buzz message and Re-Tweeting other Tweet. Twitter campaign was executed using 19 Twitter account with total 8.331 Followers. The observation time was started since August, 1st 2012 until September, 1st 2012. In the planning stage, this research using social media strategy model from Kloos as guidance to make planning strategy of UseeTV’s social media marketing. The result of this stage is a scenario of Twitter campaign. Then, the Twitter campaign program executed. After that, the campaign program is measured to see its influence to increase the number of UseeTV’s website visitor. The measurement using several social media tools, namely Tweet Level, Kred, Klout, and Google Analytic. From the research, it found a formulation in executing Twitter campaign. The finding is 24 buzzers can generate 882 website visitors. Moreover, it also found that collaboration between Twitter campaign and offline marketing can increase the result of Twitter campaign. Furthermore, in the end of the research, there are suggestions how to implement Twitter campaign effectively. Keywords: Twitter campaign, buzzer, Kloos social media strategy model, UseeTV, website visitor